Long‐term incidence of hypoglycaemia‐related events after bariatric surgery or usual care in the Swedish Obese Subjects study: A register‐based analysis. Issue 8 (25th May 2021) - Sjöholm, Kajsa; Jacobson, Peter; Taube, Magdalena; Svensson, Per‐Arne; Andersson Assarsson, Johanna C.; Carlsson, Lena M. S.; Peltonen, Markku
Abstract: Aims: To examine the incidence of hypoglycaemia‐related events over a period of up to 31 years in patients treated with bariatric surgery in the prospective, controlled Swedish Obese Subjects (SOS) study. Materials and Methods: The SOS study (n = 4047) is a prospective controlled intervention study. The present analysis included 1989 patients treated with bariatric surgery and 2027 control patients with obesity who received usual care. Diagnosed hypoglycaemia and events commonly attributed to hypoglycaemia (confusion, syncope, epilepsy and seizures), requiring hospital or specialist outpatient treatment, were identified by searching the National Patient Register. Analyses were stratified by baseline glycaemic status. Hazard ratios were adjusted for inclusion year, age, sex, smoking, glycated haemoglobin (HbA1c) level and body mass index at baseline. At the time of analysis (December 31, 2018), the median follow‐up was 22 years. Results: Compared with usual care, bariatric surgery was associated with increased incidence of hypoglycaemia‐related events in patients without baseline diabetes (168 and 219 events, respectively; log‐rank P  = .011), with a more pronounced risk during the first years of follow‐up (test of time‐treatment interaction P  = .010). Multivariate analyses in patients without baseline diabetes indicated that male sex ( P  < .001), older age ( P  = .001) and higher HbA1c levels ( P  = .006) were associated with hypoglycaemia‐related events. No association was found between risk of hypoglycaemia‐related events and bariatric surgery in patients with baseline diabetes. Conclusions: Bariatric surgery is associated with an increased incidence of hypoglycaemia‐related events in patients without baseline diabetes, especially during the first years after treatment.